Pengaruh COVID-19, Nilai Kurs dan Efek Bulan Ramadan terhadap Pengembalian Pasar Saham - Cesilia Hong, Nurainun Bangun (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to examine the effect of COVID-19, exchange rate and Ramadan month effect on stock market returns in consumer goods industry firm listed on the Indonesia Stock Exchange (IDX) in 2020. The sampling method used in this study is purposive sampling with predetermined criteria. The result of this study shows that COVID-19 that is proxied by daily death case, exchange rate and Ramadan month effect have no effect on stock market returns. COVID-19 that is proxied by daily recovered case have positive effect on stock market returns.